Perlindungan Hukum Terhadap Nasabah Cryptocurrency Di Indonesia - Karina Christiani; Arief Wibisono; Gatut Hendro TW (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
Regulation of money or currency in Indonesia is based on Law (UU) Number 7 of 2011 concerning Currency. Money is a symbol of state sovereignty that must be respected and proud of by all Indonesian citizens. In this study, the author discusses the implementation of cryptocurrency transactions in Indonesia according to the Regulation of the Commodity Futures Trading Supervisory Agency Number 5 of 2019 concerning Technical Provisions for the Implementation of the Physical Market for Crypto Assets (Crypto Assets) on the Futures Exchange, and discusses the Legal Protection in Cryptocurrency Transactions according to the Agency Regulations. Commodity Futures Trading Supervisor Number 5 of 2019 concerning Technical Provisions for the Implementation of the Physical Crypto Asset Market on the Futures Exchange in Indonesia. This writing uses descriptive qualitative method. The results of the study state that legal protection for the community is currently familiar with digital transactions and specifically during this pandemic.Keywords: Legal Protection; Cryptocurrencies; Crypto Asset AbstrakPengaturan uang atau mata uang di Indonesia didasarkan pada Undang-Undang (UU) Nomor 7 Tahun 2011 tentang Mata Uang. Uang merupakan simbol kedaulatan negara yang harus dihormati dan dibanggakan oleh seluruh warga negara Indonesia. Dalam Penelitian ini, penulis membahas mengenai Pelaksanaan Transaksi cryptocurrency di Indonesia menurut Peraturan Badan Pengawas Perdagangan Berjangka Komoditi Nomor 5 Tahun 2019 Tentang Ketentuan Teknis Penyelenggaraan Pasar Fisik Aset Kripto (Crypto Asset ) Di Bursa Berjangka, dan membahas tentang Perlindungan Hukum Dalam Transaksi Cryptocurrency Menurut Peraturan Badan Pengawas Perdagangan Berjangka Komoditi Nomor 5 Tahun 2019 Tentang Ketentuan Teknis Penyelenggaraan Pasar Fisik Aset Kripto (Crypto Asset) Di Bursa Berjangka di Indonesia. Penulisan ini menggunakan metode kualitatif deskriptif. Adapun hasil penelitian menyatakan bahwa perlindungan hukum terhadap masyarakat saat ini sudah banyak mengenal transaksi digital dan khusus dimasa pandemic ini.Kata Kunci: Perlindungan Hukum; Cryptocurrency; Crypto Asset